The Chinese entrepreneurship way : a case study approach - Perez-Cerezo, Julia (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
China is the second largest economy in the world, and it stands poised to become the largest. China's geo-political power is also developing at a stunning pace. It has been predicted that China will have more impact on the world over the next 20 years than any other country. The world order as we have known it is changing, and China is becoming its leader. But, contrary to the belief that China's economic "miracle" is solely due to its government, the reality is that it has been fuelled by its people's enormous ambitions and entrepreneurial spirit. Private-owned companies account for about 60% of the country's gross domestic product (GDP) and about 75% of the country's jobs. The real secret to the Chinese economy's outstanding development had most to do with the nature and attitude of the Chinese people.
Confucius quote -- Foreword -- Preface -- Acknowledgments -- Chinese behavior's roots -- Understanding the Chinese paradigm -- What entrepreneurship is all about, Gao Yu, Rujin -- The entrepreneurship process, Xu Xiaoyu, Bamboo Home -- Entrepreneurship by innovation in management, Yang Mianmian, Haier -- Entrepreneurship by using modern traditional Chinese medicine, Wu Naifeng, Tasly -- Entrepreneurship by using traditional Chinese culture, Liu Kecheng, Dae Joo -- Entrepreneurship by determination, Lanzhen, Tianyi -- Entrepreneurship by intuition, Xing Hui, Laote -- Entrepreneurship by perseverance, Wang Xiuyan, Haidilan -- Entrepreneurship through opportunity, Guo Feng, Dicens -- Entrepreneurship by differentiation, Chen Xiuyun, Zhu Mama -- Entrepreneurship by joint venture, Chen Yulan, Jifa -- Entrepreneurship by leveraging projects, Gong Min, Keying -- Entrepreneurship by consolidation, Zhang Ziqin, Sinolgis -- Entrepreneurship in a highly regulated sector, Huang Ying, Bank of Beijing -- Entrepreneurship by transforming traditional Chinese culture into a business, Tian Yu, Handelin -- Toward a twenty-first century entrepreneurship approach -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (pages 329-330) and index.
Title from PDF title page (viewed on November 5, 2013).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Entrepreneurship -- China -- Case studies; Chinese entrepreneurship approaches; Chinese principles and values; Chinese business culture; Chinese business attitude; Chinese business behavior; Chinese leadership styles; the Chinese paradigm; Electronic books